Problems of increasing speed and accuracy in monolithic AD and DA converters - Marcinkevicius, A.; Semys, D. (Elektronika ir Elektrotechnika, 1998)
Static and dynamic parameters of the wide-band converters are described. Methods and possibilities to improve these parameters are presented. 6-12 bit analogue-to-digital converters are theoreticaly and experimentaly investigated and demands to their constructions and technologies are formed. Methods to decrease nonlinearity of the converting characteristics are analysed and graphicaly shown. Methods and possibilities to improve dynamic parameters are analysed also. Experimentaly measured frequency band dependence on converting frequency and dynamic range of the 8-bit 100 MHz AD converter is presented. Perspectives to increase speed and velocity of such converters are reviewed.